A bistable inhibitory optoGPCR for multiplexed optogenetic control of neural circuits - Wietek, Jonas; Nozownik, Adrianna; Pulin, Mauro; Saraf-Sinik, Inbar; Matosevich, Noa; Gowrishankar, Raajaram; Gat, Asaf; Malan, Daniela; Brown, Bobbie J.; Dine, Julien; Imambocus, Bibi Nusreen; Levy, Rivka; et al. (Nature methods, 2024)
Information is transmitted between brain regions through the release of neurotransmitters from long-range projecting axons. Understanding how the activity of such long-range connections contributes to behavior requires efficient methods for reversibly manipulating their function. Chemogenetic and optogenetic tools, acting through endogenous G-protein-coupled receptor pathways, can be used to modulate synaptic transmission, but existing tools are limited in sensitivity, spatiotemporal precision or spectral multiplexing capabilities. Here we systematically evaluated multiple bistable opsins for optogenetic applications and found that the Platynereis dumerilii ciliary opsin (PdCO) is an efficient, versatile, light-activated bistable G-protein-coupled receptor that can suppress synaptic transmission in mammalian neurons with high temporal precision in vivo. PdCO has useful biophysical properties that enable spectral multiplexing with other optogenetic actuators and reporters. We demonstrate that PdCO can be used to conduct reversible loss-of-function experiments in long-range projections of behaving animals, thereby enabling detailed synapse-specific functional circuit mapping.
Online veröffentlicht: 29. Mai 2024
Gesehen am 03.02.2025